Optimizing The Utilization Of Village Funds Through The Quadruple Helix Approach: A Literature Review - Lukman Efendi; Dendy Pramana Putra; Adiwidya Muhammad Sofwan (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2023)
Village funds have become one of the alternative solutions in alleviating rural poverty in several countries, including Indonesia. The aims of this study is to identify implementations in the use of  village funds in Indonesia as a form of  village fiscal decentralization and to provide alternative strategies for optimizing village funds to achieve the goals of village fiscal decentralization. This research design is a literature review on the implementation of the utilization of village funds by using institutional databases to search for recommended journals. Based on the results of the literature review, there are several obstacles in implementing the use of  village funds including, (1) Utilization of  village funds still has weaknesses in the process of planning, organizing, implementing and controlling. In addition, in this process community participation and involvement is still not optimal, (2) There is no clear priority planning and program at the village level. Most of the village funds are used for infrastructure, so community empowerment programs tend to be sub-optimal (3) Most of the BUMDes are not in accordance with the goals and needs of the community and have not optimally empowered village communities. In its implementation, a four-actor collaboration model (quadruple helix) is recommended in this study.